The Influence of Social Media on Generation Z Consumption Patterns in Indonesia - Jihan Alyani Dirayati; Lishe Indriani Putri; Raihan Enandrisyah Zidhan; Dhiyaul Ikhsan Arthaditama (Penerbit Hellow Pustaka, 2025)
Generation Z, as digital natives, are heavily influenced by social media platforms in various aspects of their lives, including their consumption patterns. This study will analyze how exposure to social media content, such as advertising, influencer marketing, and online trends, affects Generation Z's product, brand, and shopping behavior choices. This study is expected to provide a more comprehensive understanding of Generation Z's consumption dynamics in the digital era and its implications for marketing and business strategies in Indonesia.